2020
DOI: 10.1002/fee.2276
|View full text |Cite
|
Sign up to set email alerts
|

Overview of recent land‐cover changes in biodiversity hotspots

Abstract: This is a pre-submission, non-peer reviewed, preprint for self-archiving in EarthArXiv. The revised version of this manuscript has been provisionally accepted for publication by the scientific journal Frontiers in Ecology and the Environment (https://www.esa.org/frontiers-in-ecology-and-the-environment/), and it is currently In press. Once published by the journal, the link to the publication will be made available here. The final published version of the paper might have slightly different content than the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…In comparison, range reductions in terrestrial biodiversity hotspots have often been reported to be more extensive due to anthropogenic impacts such as land use and environmental changes, leading to high extinction rates (Brooks et al, 2002;Hu et al, 2021;Kong et al, 2021;Lucas & Harris, 2021).…”
Section: Broader Implicationsmentioning
confidence: 99%
“…In comparison, range reductions in terrestrial biodiversity hotspots have often been reported to be more extensive due to anthropogenic impacts such as land use and environmental changes, leading to high extinction rates (Brooks et al, 2002;Hu et al, 2021;Kong et al, 2021;Lucas & Harris, 2021).…”
Section: Broader Implicationsmentioning
confidence: 99%
“…The Sundaland biodiversity hotspot is joined by three other biodiversity hotspots. From northeast it is connected to Philippines hotspot, east side of the Sundaland hotspot is bordering to Wallacea hotspot and Indo-Burma hotspot is joined to the northeast (Hu et al, 2021).…”
Section: Tropical Andesmentioning
confidence: 99%
“…The astounding levels of biodiversity contained in the hotspots makes them absolutely vital conservation priorities, although by definition they have suffered considerable degradation (Myers, 1988;Myers et al, 2000;Mittermeier et al, 2005). Despite their importance, Hu et al (2021) reported major, on-going degradation of the biodiversity hotspots that even extended to large areas 'protected' by legislation.…”
Section: Introductionmentioning
confidence: 99%